A thermocline thermal energy storage system with filler materials for concentrated solar power plants: Experimental data and numerical model sensitivity to different experimental tank scales. (5th May 2016) - Hoffmann, J.-F.; Fasquelle, T.; Goetz, V.; Py, X.
Abstract: Thermocline thermal energy storage is one of the most promising, cost-effective solutions in improving concentrated solar power plant capacity factor. However, this thermal energy storage needs to be well understood; for this reason, the PROMES-CNRS laboratory built a laboratory-scale experiment. The experiment comprises a thermocline thermal energy storage tank fitted with an oil loop to heat and cool down the thermal oil flowing through the tank. The present study compares experimental results coming from the laboratory experiment but also from two large scale industrial storages already presented in the literature, with two numerical models. The 1D-1P model considers a homogeneous medium that flows through the tank, while the second one (1D-2P) distinguishes between the solid continuous medium and the fluid flowing through the void fraction. The 1D-1P model showed close agreement with experimental results when compared with industrial-size tanks, but differed markedly in the case of laboratory-scale ones. The results show that the 1D-2P model is more accurate, especially for small-size tanks. Particular attention has been paid to the tank wall and to heat losses, which have a direct influence on the outlet temperature, especially for laboratory scale tanks. With these considerations, the numerical 1D-2P model can predict the thermocline behavior with accuracy, without parameter fitting process and without a high computation time.